2018
DOI: 10.3390/molecules23092343
|View full text |Cite
|
Sign up to set email alerts
|

Sanggenon C Stimulates Osteoblastic Proliferation and Differentiation, Inhibits Osteoclastic Resorption, and Ameliorates Prednisone-Induced Osteoporosis in Zebrafish Model

Abstract: Sanggenon C (SC), which is a natural flavonoid found in the stem bark of Cortex Mori, has been discovered to have the antioxidant, anti-inflammatory, and antitumor properties. However, its effect in osteoporosis has not yet been reported. In this research, the effect of SC on the proliferation of MC3T3-E1 cells was evaluated by using the MTT assay. Alkaline phosphatase (ALP) activity and the mRNA expression of Runx2, Collagen I, OPG, and RANKL were examined. TRAP-positive cell counting and bone resorption pits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
(21 reference statements)
1
14
0
Order By: Relevance
“…68 ctsk encodes a member of the cysteine protease cathepsin family and took part in the bone resorption by the destruction of the collagen matrix of the bone. 65,69 Thus, the two genes ctsk and acp5a of the RA pathway were also detected in this study. The results showed that the mRNA expression of both ctsk and acp5a were greatly decreased in EERL-treated zebrafish compared to the model group.…”
Section: Papersupporting
confidence: 66%
See 1 more Smart Citation
“…68 ctsk encodes a member of the cysteine protease cathepsin family and took part in the bone resorption by the destruction of the collagen matrix of the bone. 65,69 Thus, the two genes ctsk and acp5a of the RA pathway were also detected in this study. The results showed that the mRNA expression of both ctsk and acp5a were greatly decreased in EERL-treated zebrafish compared to the model group.…”
Section: Papersupporting
confidence: 66%
“…64 When RANK binds to RANKL, the complex can stimulate and activate osteoclast differentiation. 65 RANKL/ RANK signaling regulates osteoclast formation, activation, and survival in normal bone remodeling. 66 Thus, RANKL plays a crucial role in bone resorption.…”
Section: Papermentioning
confidence: 99%
“…It is interesting that an anticancer role of SC in inducing apoptosis of cancer cells had been observed in several previous studies [11,31]. Additionally, SC could also promote the proliferation of osteoblasts while inhibit the formation and function of osteoclasts [21]. The mechanisms underlying when and how SC switches between the pro-and anti-cell apoptosis remain elusive and deserve further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…The use of prednisone can induce bone loss. [36][37][38] In our study, we use prednisone to set up a zebrash bone loss model. Our dosing pilot study showed at the concentration of 1.00 mM, A22 didn't show obvious toxicity to the 30 zerash in the group.…”
Section: Op Therapeutic Activity In Zebrashmentioning
confidence: 99%